Pengembangan Dashboard Laporan Penjualan dan Segmentasi Pasar Komoditi Pupuk Pestisida di PT. Perusahaan Perdagangan Indonesia (Persero) Cabang Malang - Nadya Gita Chayani; Fatwa Ramdani; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT. The Malang branch of the Indonesian Trading Company (Persero) is one of the state-owned companies (BUMN) as one of the BUMNs engaged in domestic trade and international trade in the Malang region, East Java. Through the trading business of various products and commodities handled from upstream to downstream, exports and imports which are also trusted by the government to handle and maintain price stability and availability of national food stocks and or other community needs. In an effort to provide easy job evaluation and customer grouping for the marketing division, there is a recommendation for a solution in the form of a dashboard to display commodity and customer values. This system was built using the PHP programming language assisted by Boostrap and MySQL for database management. This dashboard uses data processing in the commodity database and customer data which is used as graphics and digital maps. In making a digital map using the coordinates of several areas for commodity purchases by customers in East Java province.